Peningkatan Kompetensi Guru SD PAB di Kecamatan Bandar Sribhawono Melalui Webinar Pelatihan Pemanfaatan Media Pembelajaran Berbasis Explainer Video Pada Materi Brahma Vihara - Komang Sutawan; Dittha Winyana Putra; Kadek deva Agastya; Virna Dita Pratiwi (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
The purpose of this community service activity is to improve the competence of educators in utilizing media-based learning. The focus is on Explainer video-based media, so the activity in education can be done well. Service activities are carried out through online webinars using the Zoom application. Starting with surveys, focus group discussions, demonstrations, and performances. The training material provided includes how to utilize video-based learning media on Brahma Vihara material. The results of community service activities show success, with indications of high enthusiasm and motivation to utilize explainer-based media videos by the participants at each stage of the training activity.